PENTING TATA GUNA LAHAN DALAM PENINGKATAN PENDAPATAN PETANI BERKELANJUTAN: SYSTEMATIC LITERATURE REVIEW - Eni, Eni Kusumawati; Suntoro, Suntoro; Ahmad Arif Darmawan (Fakultas Pertanian Universitas Janabadra, 2025)
Land use plays a vital role in shaping farmers’ welfare and agricultural sustainability. However, widespread unsustainable land conversion practices negatively affect farmers' income. This study analyzes the relationship between land use and farmers' income using a Systematic Literature Review (SLR) guided by the PRISMA protocol. A total of 28 scientific articles were thematically and bibliometrically reviewed. Findings show that sustainable practices, such as integrated systems (e.g., rice-crayfish farming, agroforestry), can increase income by 20–40% through diversification and efficient resource use. In contrast, unsustainable conversions (e.g., shrimp ponds, monoculture) reduce income by 15–30% due to environmental degradation and market risk. Supportive policies, including water subsidies and land tenure reforms, enhance productivity by up to 18%, while crop diversification improves income stability. Key determinants identified include the balance between sustainability and profitability, trade-offs between short- and long-term gains, and unequal access to technology. The study recommends inclusive policies, accessible innovations, and active farmer involvement. Limitations include regional bias (65% from Asia) and reliance on cross-sectional data. Future research should explore gender perspectives and innovative financing. Overall, sustainable land use is essential to improve farmers’ income and requires coordinated multi-stakeholder efforts.